2000
DOI: 10.1046/j.1365-2680.2000.00197.x
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of mechanisms involved in presynaptic inhibition of sympathetic pressor effects induced by some 5‐HT1 receptor antagonists

Abstract: 1. In a previous study, we showed that the presynaptic inhibitory action of 5-hydroxytryptamine receptor agonists on sympathetic pressor effects obtained in the pithed rats were mainly mediated by activation of 5-HT1A and 5-HT1D receptor subtypes. At the time, we observed that some 5-HT1 receptors antagonists - WAY 100,635 and NAN-190 (both 5-HT1A receptor antagonists), methiothepin (a 5-HT1,2,5,6,7 receptor antagonist) and spiperone (a 5-HT1,2 receptor antagonist) - reduced per se the pressor effects obtained… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
4
0

Year Published

2002
2002
2014
2014

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 43 publications
1
4
0
Order By: Relevance
“…These observations, along with our findings that injection of this compound induced a decrease in blood pressure in the anaesthetized rat, suggest that WAY 100635‐induced hypotension could be related to vascular α 1 ‐adrenoceptor blockade. In support of this contention, we found that WAY 100635 significantly shifted the phenylephrine pressor effect to the right in the pithed rats, at a dose of 1 mg kg −1 , with no significant effects at lower antagonist doses; similar dose‐related effects have been observed when WAY 100635 antagonized the increase in mean blood pressure induced by electrical stimulation, but not by noradrenaline administration where WAY 100635 did not modify the increase in blood pressure elicited by the catecholamine (Fernandez, Calama, Moran, Martin & San Roman, 2000). We do not know why phenylephrine‐induced pressor effects were blocked by WAY 100635 and those for noradrenaline were not, but a possible explanation could be that phenylephrine acts on α 1 ‐adrenoceptors (and probably on β‐adrenoceptors), while noradrenaline acts on all three adrenoceptors, and part of its pressor effect may be due to α 1 ‐adrenoceptor stimulation.…”
Section: Discussionsupporting
confidence: 65%
See 1 more Smart Citation
“…These observations, along with our findings that injection of this compound induced a decrease in blood pressure in the anaesthetized rat, suggest that WAY 100635‐induced hypotension could be related to vascular α 1 ‐adrenoceptor blockade. In support of this contention, we found that WAY 100635 significantly shifted the phenylephrine pressor effect to the right in the pithed rats, at a dose of 1 mg kg −1 , with no significant effects at lower antagonist doses; similar dose‐related effects have been observed when WAY 100635 antagonized the increase in mean blood pressure induced by electrical stimulation, but not by noradrenaline administration where WAY 100635 did not modify the increase in blood pressure elicited by the catecholamine (Fernandez, Calama, Moran, Martin & San Roman, 2000). We do not know why phenylephrine‐induced pressor effects were blocked by WAY 100635 and those for noradrenaline were not, but a possible explanation could be that phenylephrine acts on α 1 ‐adrenoceptors (and probably on β‐adrenoceptors), while noradrenaline acts on all three adrenoceptors, and part of its pressor effect may be due to α 1 ‐adrenoceptor stimulation.…”
Section: Discussionsupporting
confidence: 65%
“…The lack of correlation in cardiovascular effects of WAY 100635 in both animal models may involve vascular α 1 ‐adrenoceptor blockade by WAY 100635 in pithed rats, while in anaesthetized rats, besides vascular α 1 ‐adrenoceptor antagonism there could be other mechanism. These could include inhibition of noradrenaline release from sympathetic nerve terminals, via stimulation of presynaptic 5‐HT 1A receptors, as a partial agonist as has been suggested in 5‐HT 1A receptor transfected cells (Welsby, Kellett, Wilkinson & Milligan, 2002), presynaptic α 2 ‐adrenoceptor stimulation (Fernandez, Calama, Moran, Martin & San Roman, 2000), or interaction with other 5‐HT receptors involved in cardiovascular function (5‐HT 7 ? ).…”
Section: Discussionmentioning
confidence: 99%
“…A nonselective 5‐HT 1 antagonist, methiothepin (Hoyer et al ., 1994) blocked the electrically induced pressor responses per se , and this inhibitory effect may be accounted for the affinity of this antagonist for α 1 ‐adrenoceptors (Leysen et al ., 1985; Fernández et al ., 2000). In this sense, the inhibition of electrically induced pressor responses by 5‐HT (10 μ g kg −1 min −1 ) was unable to be elicited after i.v.…”
Section: Discussionmentioning
confidence: 55%
“…The methods used in the present study are related to those implemented in other investigations performed by our group, 17,18 in which we examined total sympathetic stimulation in pithed rats or cardiac stimulation. In such cases, we placed electrodes for electrical stimulation in the stainless steel rod used to pith the rats but, because in the present study we were interested in the hindquarter vascular bed, we had to stimulate this by placing the electrodes in the lumbar sympathetic chains.…”
Section: Animal Preparationsmentioning
confidence: 99%